Advances in biochar carbonization regulation and remediation of soil heavy metals - LIAO Wei; ZHANG Xiong*; YANG Haiping*; SHAO Jingai; ZHANG Shihong; CHEN Hanping (能源环境保护)
Biochar has vast potential for application in the remediation of heavy metals (HMs) in soil. The remediation effect depends on the physicochemical characteristics of biochar and the soil environment. Exploring the mechanisms of biochar regulation and its ability to retain HMs can provide guidance for optimizing the biochar preparation process. This paper summarizes the changes in the physicochemical properties of biochar under varying preparation methods, explains the primary mechanism of HMs immobilization, and reviews the effects of biochar aging on its physicochemical properties. The main mechanisms of HMs adsorption by biochar in soil include pore adsorption, cation exchange, functional group complexation, and mineral precipitation. The relative importance of different adsorption mechanisms depends on factors such as pyrolysis temperature, raw material, residence time, and atmosphere. Additionally, biochar aging leads to changes in its physicochemical properties, such as pore breakage, decomposition of oxygen-containing functional groups, and unstable carbon precipitation. Different aging factors have varying impacts on biochar. Exploring the mechanisms of various aging factors and their effects on HMs adsorption, coupled with an in-depth examination of the pyrolysis process and carbon formation mechanism, can minimize the impact of environmental factors on the effectiveness of HMs adsorption. Furthermore, this paper proposes future directions for biochar application, aiming to provide a reference for evaluating the effectiveness of biochar and guide its application in remediating HMs contaminated soil.